The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1016/s0893-133x(02)00320-2
|View full text |Cite
|
Sign up to set email alerts
|

Supraphysiological Doses of L-Thyroxine in the Maintenance Treatment of Prophylaxis-Resistant Affective Disorders

Abstract: This prospective open-label study examined the efficacy of adjunctive supraphysiological doses of L-thyroxine (T 4 ) in the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 31 publications
(19 reference statements)
0
62
0
1
Order By: Relevance
“…Although SPCs of T3 have been used in the treatment of chronic fatigue syndrome, 29 prophylaxis-resistant psychiatric illnesses, [30][31][32] and obesity, 33,34 the mechanism of T3 action at such concentrations is not known. Here, we focused our study on the role of SPCs of T3 in modulating cellular stress signaling pathways and stress-mediated antiviral responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although SPCs of T3 have been used in the treatment of chronic fatigue syndrome, 29 prophylaxis-resistant psychiatric illnesses, [30][31][32] and obesity, 33,34 the mechanism of T3 action at such concentrations is not known. Here, we focused our study on the role of SPCs of T3 in modulating cellular stress signaling pathways and stress-mediated antiviral responses.…”
Section: Discussionmentioning
confidence: 99%
“…24 An earlier report has indicated that thyroid hormone receptor (THR) agonist triiodo-l-thyronine (T3) at physiological concentrations can potentiate the inhibition of vesicular stomatitis virus (VSV) replication by IFN-g; 28 however, these authors did not observe any inhibition of VSV replication by T3 alone. Although supraphysiological concentrations (SPCs) of T3 have been used in the treatment of chronic fatigue syndrome, 29 prophylaxis-resistant psychiatric illnesses, [30][31][32] and obesity, 33,34 the mechanism of T3 function at SPCs and their role in modulating cellular stress pathways and stress-mediated antiviral responses are unknown. In this paper, we report that T3 hormone at SPCs activates ISR pathways that include PKR activation, SG formation, and activation of ER-mediated stress pathways.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 In this regard, adjunctive use of levothyroxine (L-T 4 ) at supraphysiological doses offers promise for patients who suffer rapid cycling [3][4][5][6] and prophylaxis-resistant bipolar disorders, [6][7][8][9] for patients with bipolar and unipolar disorder during a phase of refractory major depressive episode, 10 and patients with refractory chronic depression and dysthymia. 11 Despite knowledge of the role of thyroid hormones in the maturation and the differentiation of the brain, 12,13 and the association between thyroid status and behavioral disturbances in thyroid disease, 14,15 the action of thyroid hormones in the adult brain has received comparatively little attention.…”
mentioning
confidence: 99%
“…56 ) In aggregate, only 29 subjects, some of whom were unipolar depressives, all from the same research group, have been evaluated in the studies published over the last 15 years. [57][58][59] (Some of the subjects in two earlier reports 57,58 are included in the later paper. 59 ) Nonetheless, high-dose thyroid hormone augmentation continues as a potential option for treatment-resistant bipolar disorder.…”
Section: High-dose Thyroid Augmentationmentioning
confidence: 99%
“…Mean doses of Lthyroxine in the two recent publications were 379 59 and 482 mcg, 58 between 3 and 4.5 Â the daily thyroid replacement dose in the United States. Thus, patients were treated with supraphysiological doses.…”
Section: High-dose Thyroid Augmentationmentioning
confidence: 99%